Evaluasi Kualitas Spermatozoa Kambing Boer Dengan Penambahan Ekstrak Bunga Telang (Clitoria ternatea) Dalam Pengencer Skim Kuning Telur: Evaluation of Boer Goat Spermatozoa Quality with the Addition of Butterfly Pea Flower Extract in Skim Milk Egg Yolk Extender (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2026)
This study aims to evaluate the addition of butterfly pea flower extract as a natural antioxidant source in Skim Milk with Egg Yolk on the quality of Boer goat spermatozoa. The study used a Randomized Block Design (RBD) with five treatments and four replicates, and the data were further analyzed using Duncan's test. The treatments consisted of sperm added to skim milk (control, P0) and to skim milk with egg yolk, with the addition of butterfly pea flower extract at various doses (P1 = 2 mL, P2 = 4 mL, P3 = 6 mL, P4 = 8 mL). The parameters observed were motility, viability, abnormality, and intact plasma membrane. The results showed that the addition of butterfly pea flower extract had a significant effect (p